Low Technological competence as barrier to online teaching and its impact on anxiety among teachers during Movement Control Order in a rural district in Terengganu, Malaysia - CW Ahmad, Che Wan Aisyah Azizah; Zainal Abidin, Emilia; Ismail, Noor Hassim (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2021)
Introduction: Teachers are among the occupation most affected due to COVID-19 pandemic in which they are forced to navigate through full online teaching and learning process due to the implementation of Movement Control Order (MCO). This study aims to determine the prevalence of psychological symptoms and its predictors during COVID-19 MCO among primary school teachers in rural Terengganu, Malaysia. Methods: A total of 239 teachers from 17 primary schools were recruited. Depression, Anxiety and Stress Scale (DASS) questionnaire was employed to measure to psychological problems. Online questionnaire was used and data were analysed using statistical software. Results: Majority of respondents was female (80%) with a mean (standard deviation) age of 43 (7.37). Approximately 14%, 20% and 8% of teachers reported depressive, anxiety and stress symptoms. The reporting of anxiety was contributed by low technological competence (Adjusted Odds Ratio, AOR) 4.46; 95% Confidence Interval, CI: 1.03- 19.34). Other factors include not living with in-laws (AOR 0.12; 95% CI: 0.01-0.96) that were linked with depression and diagnosed with chronic diseases (AOR 4.54; 95% CI: 1.16-17.88) that were linked with stress. Conclusion: Low technological competence was a significant barrier to online teaching during MCO and is linked to anxiety among teachers. There is the need to ensure continuous provision of targeted upskilling programs specific for the current online learning landscape and support system to address mental health problems. This will entitle teachers to pursue work without detrimental impacts on mental health.